2013
DOI: 10.1038/srep02998
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome comparison of donor and cloned dogs

Abstract: Cloning is a process that produces genetically identical organisms. However, the genomic degree of genetic resemblance in clones needs to be determined. In this report, the genomes of a cloned dog and its donor were compared. Compared with a human monozygotic twin, the genome of the cloned dog showed little difference from the genome of the nuclear donor dog in terms of single nucleotide variations, chromosomal instability, and telomere lengths. These findings suggest that cloning by somatic cell nuclear trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(31 reference statements)
2
9
0
Order By: Relevance
“…We mapped Illumina short read libraries from a diverse collection of 118 publically available canid genomes to the Li et al canine Y-chromosome assembly (Additional file 1 : Table S1). This sample set includes 1 coyote [ 17 ], 13 wolves [ 4 , 17 20 ], 30 village dogs including samples from India, Portugal, Nigeria, and China [ 4 , 21 , 22 ], and 74 breed dogs [ 4 , 19 25 ]. Based on metrics such as raw read depth, MQ0-to-depth ratio, and the apparent presence of heterozygous variant calls, we identified 484,924 positions on the Y assembly amendable to variant identification using short-sequencing reads (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We mapped Illumina short read libraries from a diverse collection of 118 publically available canid genomes to the Li et al canine Y-chromosome assembly (Additional file 1 : Table S1). This sample set includes 1 coyote [ 17 ], 13 wolves [ 4 , 17 20 ], 30 village dogs including samples from India, Portugal, Nigeria, and China [ 4 , 21 , 22 ], and 74 breed dogs [ 4 , 19 25 ]. Based on metrics such as raw read depth, MQ0-to-depth ratio, and the apparent presence of heterozygous variant calls, we identified 484,924 positions on the Y assembly amendable to variant identification using short-sequencing reads (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final sample set contained 118 samples including 1 coyote [ 17 ], 13 wolves [ 4 , 17 20 ], 30 village dogs including samples from India, Portugal, Nigeria, and China [ 4 , 21 , 22 ], and 74 breed dogs [ 4 , 19 25 ]. We note that this set includes two Afghan Hounds which are clones of each other and therefore have identical Y-chromosome sequences [ 25 ]. We next recalled Y-chromosome genotypes in the male samples using the GATK haplotype caller using the EMIT_ALL_SITES flag.…”
Section: Methodsmentioning
confidence: 99%
“…For cloned animals, a recent study on a cloned dog showed little difference from the genome of the nuclear donor dog in terms of single nucleotide variations, chromosomal instability and telomere lengths . Further research may provide useful information on the utilization of this region as markers for identity.…”
Section: Significance Of Analytical Testingmentioning
confidence: 99%
“…For example, a cell line with aberrant genetic material led to accelerated aging in 3 cloned pigs [35] . On the other hand, whole-genome comparison of a cloned dog and its respective nuclear donor showed less de novo differences than between 2 human monozygotic twins [4] , showing that in SCNTderived animals the DNA can be conserved to a very high level.…”
Section: Genomic Changes In Nuclear and Mitochondrial Dnamentioning
confidence: 99%
“…While individual germ cells do age along with its organism, various control and selection mechanisms assure that the next generation starts relatively "unchanged" and healthy [2,3] . It is, for example, now known that both nuclear and mitochondrial genomes are likely to acquire a small number of mutations between parents and offspring [4] . We regard this minimal change that occurs during natural reproduction, within the physiological reproductive lifespan of the parents, as the ideal 'reset to zero' of the aging clock, against which the aging of cloned animals has to be compared.…”
Section: Introductionmentioning
confidence: 99%